Analysis the impact of advertising towards purhasing futsal shoes (case study Kelme futsal shoes ) / Ahmad Mustaqim Mohamad - Mohamad, Ahmad Mustaqim (2015)
The purpose of this review is to examine and analyze the impact of advertising towards purchasing futsal shoes. An advertising campaign is a specific course of action design to advertise. The advertisements planned will appear throughout the Malaysia. In order to have an effective campaign the focus will be on the bigger urban and multicultural cities. We plan to expose our target audience to Kelme brand via various outlets throughout their daily lives so that we are present in player futsal minds. This analysis will be more focus on advertising campaign using TV-Commercial and print ads. Teenagers are now more knowledgeable.They are truly the internet generation, and get their news and information primarily from television. The television medium is the most attractive and important place to advertise.Most of the young people remain glued to the television and enjoy what they see. We will appeal to our target audience by producing TV-Commercial ads that reflect the style of playing futsal. We will also show the advantages and the latest technology on these shoes.The campaign theme that will be used is durable, quality, comfort and style.